Effects of plasma technique and gamma irradiation on seed germination and seedling growth of chili pepper - Monthida Thisawech (2020)
© 2020, Chiang Mai University. All rights reserved. The effects of plasma technique and gamma irradiation on seed germination, seedling growth and desirable traits of chili pepper for breeding program were investigated. In the plasma technique, the seeds were treated with the argon plasma. The argon plasma was driven by high voltage DC pulse at 25 kHz, plasma dissipated powers were 0.41 to 0.61 watt and argon gas flow rate of 3 standard liters per minute for 15 sec. The treated seeds including control were sown in the tray and kept in a green house in completely randomized design (CRD) with 3 replications. At 1 week after sowing, the highest of seed germination percentage was found on plasma dissipated powers 0.48 watt, significantly. Seedlings at 8 weeks were shown non-significantly in height, diameter of canopy and number of leaf. These results indicated that plasma treatment might promote the seed germination while, the growth of seedling was not different with control. In gamma irradiation, the seeds were treated with gamma ray in 150 to 600 gray. The results showed that seed germination percentage and survival percentage were different significantly. The growth of seedlings in height, diameter of canopy and number of leaf were differed with control. Plasma treatments and gamma irradiation were effects on seed germination and seedling growth of chili pepper. This data will be useful for chili pepper improvement further.